Pola Pengembangan Sumber Daya Manusia di Andalusia Mumtaza dalam Mewujudkan Santri yang Unggul - Siregar, Lukmanul Hakim; Sutanto, Aftoni (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research aims to explore patterns of human resource development at the Andalusia Mumtaza Islamic Boarding School, Huta Baru Village and its impact on student achievement. The research method used is a qualitative descriptive approach. The research results show that although there is a shortage of professional workers, the implementation of human resource development in Islamic boarding schools is still not organized effectively. The problem of functional relationships between functions in schools is also a challenge. Improving human resources starts from planning which includes needs, development goals and implementation methods. Recruitment and training programs, such as on-the-job training, ICT and Arabic language training, are an integral part of the implementation phase. An assessment is then carried out to monitor changes in students' attitudes and behavior. Supporting factors, such as workforce, facilities and infrastructure, play an important role, but limited funds/activities are an obstacle in managing the development of the Islamic boarding school's workforce.